Rational Design of Multifunctional Feγ-Fe2 O3 @H-TiO2 Nanocomposites with Enhanced Magnetic and Photoconversion Effects for Wide Applications From Photocatalysis to Imaging-Guided Photothermal Cancer Therapy - Wang, Meifang (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.